Manajemen Sarana dan Prasarana di MSI 19 Kebulen - Naufal, Nabil; Hanif, Mamun (Jurnal Manajemen Pendidikan Islam (MANAPI), 2024)
This research examines how to manage the facilities and infrastructure found in school. The aim of this research is to determine the use and maintenance of educational facilities. This research approach is qualitative with a descriptive approach. Data sources in research these are school principals, facilities and infrastructure managers, teachers and students. Data collection technique through observation of research results and discussion it can be concluded that school facilities and infrastructure Very influential on student learning outcomes, if the facilities and infrastructure available at the school complete, then learning will run optimally. Educational facilities include classrooms, media learning, tables, chairs and others. Meanwhile, infrastructure is an indirect facility functions to support learning activities such as courtyards, roads in schools. The existence of facilities and This school infrastructure is a tool to support the success of the process carried out by the school as an effort provide services to the public, because without suggestions and infrastructure in schools, the learning process will fail teaching teachers and students cannot run well and the expected results will not be achieved. The facilities and infrastructure at MSI 19 Kebulen come from government assistance channeled through Department of Religion, community assistance and foundations. Keywords: Management, Facilities and Infrastructure, MSI 19 Kebulen.